Committee of Sponsoring Organization of the Treadway Commission (COSO) Framework as a Control Framework Construction Internal Sharia Based - Djasuli, Mohamad; Triyuwono, Iwan; Purwanti, Lilik; Roekhudin, Roekhudin (Budapest International Research and Critics University, 2022)
COSO internal control Framework is an operational activity that is widely used for more effective and efficient performance. The purpose of this study is to analyze internal control based on the COSO Framework concept and the concept of Islamic sharia and a comparison between the two. The method used in this research is descriptive qualitative with a database of phenomena and the substance of the meaning of the phenomenon. The findings in this study that the COSO Framework as an internal control system that is proven to be effective and can uncover various cases of violations that occur in the world, both at the organizational and government scale. In principle the COSO Framework 's internal control concept based on the principle of distrust of the organizational hierarchy (management, board of directors, employees, shareholders) . On the other hand, the concept of internal control based on the concept of Islamic sharia is based on aspects of one's spirituality and religiosity (tawhid and taqwa). The concept of Islamic internal control is not based on fear of rule of law, control, people should have faith that everything they do is supervised by God and will be accounted for in life after life with inner awareness. Comparison of the concept of internal control between COSO Framework and Islam in principle are not contradictory, but the concept of Islamic internal control is complementary and fills the empty space in the COSO internal control concept. Tawhid and Taqwa are the first foundations of the COSO Framework which will have a major impact on the successful implementation of the COSO Framework within the organization or institution to prevent everyone in every element in the organization and institution from doing bad or wrong things.